Novecento d’acqua e di terra. Il Tennis Club di Giovanni Muzio a Milano - Lisini, Caterina (Firenze Architettura, 2019)
In Muzio’s Tennis Club in Milan there is an evident reference to the classical tradition in architecture and to the use of compositive modules and figures typical of the 20th century in Milan. However, in the swimming pool complex there is also the presence of the contemporary research of metaphysical painting, which results almost in a meeting point between his work from the Twenties and his later mature masterpieces.